Performance of Ladle Furnace Slag in Mortar under Standard and Accelerated Curing - Iffat Sultana; G. M. Sadiqul Islam (Advances in Civil Engineering, 2022)
This research preliminarily investigated the suitability of a locally available ladle furnace slag (LFS) as a partial replacement of cement in mortar. The raw material was first characterized to obtain its chemical and physical properties through particle size distribution, X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Later, the raw LFS was classified into two categories: (i) raw LFS and (ii) sieved (passing through #200 sieve) LFS and incorporated in mortars as a partial replacement of cement. Mortar prisms with 5, 10, 15, 20, 25, and 50% LFS (raw and sieved) were prepared and cured under normal temperature (NTC) for 7, 28, and 56 days. Additional mortar prisms (with raw and sieved LFS) were prepared by curing them under high-temperature accelerated curing (HTAC) for 7 days. The characterization tests suggest that CaO, SiO2, MgO, and Al2O3 are the main compounds of raw LFS used in this study. The mineralogical phases present in the raw slag are calcio-olivine, akermanite, α-quartz, merwinite, magnetite (Fe3O4), and calcium-aluminium oxide. Both raw and sieved LFS-blended mortars yield good consistency up to 25% cement replacement in mortars. The compressive strength of NTC mortar suggests that 5% and 10% replacement of cement with raw and sieved LFS yields higher strength than the control mortar. Seven days strengths of raw and sieved LFS blended mortars obtained for HTAC are closely comparable to that of 28 days under NTC. This study recommends that LFS could be a sustainable supplementary material to use as a partial replacement of cement in mortar, preferably up to a level of 15% for standard works.